Implementation of enhanced recovery after surgery for caesarean delivery: a quality improvement initiative - Melissa Walker; Nancy Watts; Jose C A Carvalho; Ella Huszti; Sara Santini; Mara Sobel; Naveed Siddiqi; Nighat Jahan; Kim Dart; Stella Wang; Jackie Thomas (BMJ Open Quality)
Background Enhanced recovery after caesarean delivery (ERAC) is a multidisciplinary, evidence-based bundle of interventions developed from Enhanced Recovery After Surgery principles, designed to improve patient outcomes, reduce complications and save healthcare resources. Despite these benefits, the implementation of ERAC within the Canadian healthcare context is unknown. In addition, previous ERAC studies typically excluded patients undergoing unplanned caesarean deliveries (CD). The objective of our study was to evaluate the results of a quality improvement initiative that implemented a comprehensive ERAC pathway for both planned and unplanned CD in a large Canadian obstetric unit, with a specific focus on patient-reported outcomes.Methods A pre-implementation post implementation design was used. The primary outcomes were Obstetric Quality of Recovery Score (ObsQoR-10) and patient satisfaction at 6 weeks postpartum. Secondary outcomes included postpartum length of stay, postoperative pain and maternal infectious morbidity.Intervention Antenatal, intraoperative and postoperative ERAC bundles were developed with multidisciplinary input.Results 513 patients were included: 290 pre-implementation (149 planned CD, 141 unplanned CD) and 223 post- implementation (128 planned CD, 95 unplanned CD). Baseline demographics were similar, except the post implementation groups had significantly higher median Body Mass Index (BMI). In planned CD, ObsQoR-10 scores were on average 3.4 points higher in the post-implementation group (95% CI (−0.19 to 6.99); p-value=0.063). Patient satisfaction assessed at 6 weeks postpartum was significantly improved by 12 points in the post-implementation group (95% CI (5.58 to 18.62); p-value<0.001). In unplanned CD, implementation was not associated with ObsQoR-10 (p-value=0.92) or patient satisfaction assessed at 6 weeks postpartum (p-value=0.43). Pain scores were higher in both post-implementation groups, but there were no differences in morphine milliequivalents or requirement for breakthrough opioids. Length of stay and maternal infectious morbidity were similar.Discussion Implementation of ERAC in a large Canadian tertiary care obstetrics unit was feasible and resulted in improved recovery and increased satisfaction in patients undergoing planned CD. There were no differences in other outcomes, including infectious morbidity; however, the contribution of BMI needs to be explored. Patients undergoing unplanned CD face additional challenges related to outcomes, recovery and satisfaction and should be targeted in future studies.